The Study on Awareness of Empowering Minds: The Role of Psycho-Education in Mental Health - Binish Nawaz; Neeta Maheshwary; Arjumand Ahmed; Muhammad Iqbal Asif; Syed Awais Aftab; Muhammad Aman Hasan (Liaquat National Journal of Primary Care)
Mental health disorders pose a significant public health challenge in Pakistan, with high prevalence rates and adverse impacts on individual well-being and societal functioning. This abstract highlights key findings from available research on mental disorders and mental health prevention in Pakistan, drawing upon relevant studies to inform future interventions and policy initiatives. Studies have identified common mental health disorders such as depression, anxiety, and post-traumatic stress disorder (PTSD) among the population, with intimate partner violence emerging as a significant risk factor for psychological distress. Psychological distress is also associated with physical morbidity, highlighting the interconnectedness of mental and physical health outcomes. Preventive interventions, including awareness campaigns, community-based programs, and access to mental health services, are essential to address the burden of mental illness and reduce stigma. These initiatives aim to promote early detection, increase help-seeking behavior, and provide timely support to needy individuals. However, further research and collaborative efforts are necessary to develop culturally appropriate interventions that address the unique challenges faced by individuals and communities in Pakistan and improve overall mental health outcomes.